EDUKASI MANAJEMEN STRES SAAT BELAJAR KEPADA PESERTA DIDIK SMP N 36 SURABAYA DAN SMA N 10 SURABAYA DALAM MENGHADAPI PEMBELAJARAN JARAK JAUH DAN PASCA PANDEMI COVID-19 - Safira Rizka Lestari; Ramadhani Mahendra Kusuma; Mitha Anggisna Angreini; Haryo Sulistiyantoro; Yudi Nur Supriadi (LPPM Universitas Bina Bangsa, 2022)
The effort to stop the spread of the Covid-19 virus in the education sector is to implement the Distance Learning system so that the teaching and learning process is carried out online. As the rate of spread of the Covid-19 virus decreases, offline learning or Face-to-face Learning is now starting to be implemented again. The city of Surabaya is one of the regions in Indonesia that has made the transition from online to offline learning. Based on a preliminary survey conducted among students of SMP N 36 Surabaya and SMA N 10 Surabaya, there are several obstacles faced during online and offline learning including the inability of students to manage stress so that learning time is inefficient. Therefore, stress management education activities were carried out while studying for students at SMP N 36 Surabaya and SMA N 10 Surabaya in Facing Distance Learning and Post-Covid-19 Pandemic. This activity was attended by 33 students of SMP N 36 Surabaya and 28 students of SMA N 10 Surabaya. The activity is carried out in several stages, namely, the preparation stage, the implementation stage, and the evaluation stage. Based on the service activities that have been carried out, all students from SMP N 36 Surabaya and SMA N 10 Surabaya participated in stress management education activities while studying until the end of the activity. Students from both schools were able to recognize or identify the symptoms of stress shown by the results of a simple questionnaire